2019
DOI: 10.1177/1534734619878090
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin and Amputation Risk: Evidence So Far

Abstract: The CANVAS program detected a 2-fold increased risk of lower limb amputation in patients treated with canagliflozin compared with those with placebo. This adverse effect was not confirmed in the CREDENCE trial. Moreover, randomized controlled trials with other agents in this class, dapagliflozin and empagliflozin, did not detect increased risk of amputation. Observational studies, cohort studies, and pharmacovigilance reports with sodium-glucose cotransporter 2 inhibitor (SGLT2i) have reported conflicting resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…8 Canagliflozin trials found an increased incidence of lower-limb amputation. 9 However, subsequent studies have not replicated these findings. As a drug class SGLT2 inhibitors do not appear…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…8 Canagliflozin trials found an increased incidence of lower-limb amputation. 9 However, subsequent studies have not replicated these findings. As a drug class SGLT2 inhibitors do not appear…”
Section: Discussionmentioning
confidence: 97%
“…This led the FDA to recommend postmarketing surveillance studies 8. Canagliflozin trials found an increased incidence of lower-limb amputation 9. However, subsequent studies have not replicated these findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brookes et al 2 have shown that nutritional deficiencies may predict diabetic foot amputations. Relevant to amputations, Papadokostaki et al 3 provide a review of amputation risk associated with the antidiabetic drug canagliflozin. Salutini et al 4 conducted a survey among Italian experts to achieve a consensus on diabetic foot management.…”
mentioning
confidence: 99%